2010
DOI: 10.1186/1471-2229-10-31
|View full text |Cite
|
Sign up to set email alerts
|

Novel induced mlo mutant alleles in combination with site-directed mutagenesis reveal functionally important domains in the heptahelical barley Mlo protein

Abstract: BackgroundRecessively inherited natural and induced mutations in the barley Mlo gene confer durable broad-spectrum resistance against the powdery mildew pathogen, Blumeria graminis f.sp. hordei. Mlo codes for a member of a plant-specific family of polytopic integral membrane proteins with unknown biochemical activity. Resistant barley mlo mutant alleles identify amino acid residues that are critical for Mlo function in the context of powdery mildew susceptibility.ResultsWe molecularly analyzed a novel set of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 36 publications
2
69
0
7
Order By: Relevance
“…Interestingly, when displayed in the evolutionary trees of MLO protein family, all MLO isoforms from dicots experimentally shown to be necessary for PM immunity group in the clade V in the scientific documents [ [8][9][10][20][21][22] ]. Furthermore, clade IV harbors all featured monocot PM perceptivity proteins [ 23 ]. These show that phylogenetic studies on MLO proteins may predict factor candidates for PM perceptivity.…”
Section: Introductionmentioning
confidence: 80%
“…Interestingly, when displayed in the evolutionary trees of MLO protein family, all MLO isoforms from dicots experimentally shown to be necessary for PM immunity group in the clade V in the scientific documents [ [8][9][10][20][21][22] ]. Furthermore, clade IV harbors all featured monocot PM perceptivity proteins [ 23 ]. These show that phylogenetic studies on MLO proteins may predict factor candidates for PM perceptivity.…”
Section: Introductionmentioning
confidence: 80%
“…1 a), which might facilitate PM resistance conferred by CmMLO genes. As the second and third cytoplasmic loops of MLO proteins play a critical role in powdery mildew susceptibility [40], any mutation of these positions might be involved in PM resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The invariable cysteine and proline residues in extracellular loops or in TM domains are necessary for MLO protein function and/or durability [11]. In addition, second and third cytoplasmic loops in MLO proteins are important for PM susceptibility [40]. Moreover, histological reports…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of the mlo transcript was also detected in rice infected with blast fungi and in wheat injected with powdery mildew-derived carbohydrate (Piffanelli et al, 2002). Recently, using Mlo mutant alleles in barley, Reinstädler et al (2010) revealed the regions of the MLO protein that are functionally important for resistance to powdery mildew. However, microarray analyses found that not only the Mlo genes but also more than 300 other genes showed expressional changes after powdery mildew infection in barley, and some of them were…”
Section: Introductionmentioning
confidence: 99%